2006
DOI: 10.1111/j.1095-8649.2006.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of the deep‐sea flatfish Lepidorhombus boscii in north‐eastern Mediterranean waters

Abstract: Stomach content analysis of four-spotted megrim Lepidorhombus boscii in the oligotrophic Aegean Sea revealed that specimens with fully filled stomachs were rarely encountered. The overall dietary breadth of the species appeared to increase in winter and spring, when stomachs fullness was reduced. The species exhibited a relatively high trophic diversity and could be considered a euryphagous carnivore preying mainly upon crustaceans. Decapod natants, namely Processa canaliculata and Alpheus glaber, dominated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
3
11
0
1
Order By: Relevance
“…The present study showed that feeding activity was higher in summer, the females showed lower vacuity values than males and the largest individuals had lower feeding activity than the smallest ones. This feeding behaviour is consistent with the findings of several authors (Belghyti et al, 1993;Vassilopoulou, 2006;de Juan et al, 2007). However, some authors (Redon et al, 1994;Morte et al, 1999;de Juan et al, 2007) have reported that the vacuity index was highest in spring-summer.…”
Section: Dietsupporting
confidence: 82%
See 3 more Smart Citations
“…The present study showed that feeding activity was higher in summer, the females showed lower vacuity values than males and the largest individuals had lower feeding activity than the smallest ones. This feeding behaviour is consistent with the findings of several authors (Belghyti et al, 1993;Vassilopoulou, 2006;de Juan et al, 2007). However, some authors (Redon et al, 1994;Morte et al, 1999;de Juan et al, 2007) have reported that the vacuity index was highest in spring-summer.…”
Section: Dietsupporting
confidence: 82%
“…azevia showed a broader diet spectrum than the other three flatfish species, according to season, sex and size class. The diet breadth of M. azevia was higher in seasons when the feeding activity was lowest, which could correspond to a balance to compensate the decrease in prey availability during these seasons (Vassilopoulou, 2006).…”
Section: Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide range of prey items and high dietary diversities may be indications of their generalized and opportunistic feeding habits. Many flatfishes, including Cynoglossus species, can be classified as generalist feeders, with their diets composed of a wide variety of preys (Dou 1995;Gibb 1997;Cabral et al 2002;Vassilopoulou 2006). These generalized feeding habits appear to be common phenomena in flatfish.…”
Section: Discussionmentioning
confidence: 99%